(untitled) (Al-Academy, 2021)
There is no doubt that each of the arts has a material from which the aesthetic achievement is built, so the researcher found that the art of theater, especially the show, whose artistic achievement is based on the body of the actor who emits the formal language (body language), is the focus of interest and active presence, because the body possesses its spiritual qualities that made him and the ability to The formation of things by (his body language), so the researcher studied this theatrical phenomenon and divided it into four chapters. In the first chapter, the research problem included the following question: (Is there a phenomenon of body language in the contemporary theatrical show "Imagine that" as a model) so It is of cognitive importance as it provides an objective study for researchers in theater sciences at the level of directing and acting, as well as the aim of the research (to identify the body language and what this phenomenon carries in the theatrical presentation ((Imagine that)) as a model) and the first chapter ended with defining the terms, and in the second chapter The theoretical framework as it included two studies in the first topic, the researcher dealt with (the concept of the body language phenomenon) from a general standpoint, and the second topic (theatrical body language) and how this physical phenomenon was linked to theatrical art, and the chapter concluded with the most important indicators that resulted from the theoretical framework, and then The third chapter, which includes the procedures and consists of the research community, the research sample and the research tool, and the sample analysis, and finally the fourth chapter: it included the results, conclusions, recommendations and proposals, and then the sources, references and a summary in Arabic and English